Utilization of Web Design-Based E-Booklet as Local History Teaching Material at SMKN 10 Malang - Dewa Agung Gede Agung; Nadya Rahmah; Nur Elifianita Susanti; Aprilia Iva Swastika; Prasepti Andriani (UNIVERSITAS MUHAMMADIYAH METRO, 2026)
The utilization of web design-based ebooklets in the learning process is a strategic step as an innovative educational tool to improve students' learning experience. Web design-based ebooklets are easily accessible and cost-effective so that they are suitable for students to use in learning history, especially local contexts with a focus on the Major Hamid Rusi Monument. This research departs from the potential and problems encountered at SMKN 10 Malang which aims to examine the utilization of Web design-based ebooklets as local history teaching materials at SMKN 10 Malang, with a case study of the Major Hamid Rusdi Monument. The research uses a case study method and a qualitative approach that explores how the Ebooklet can help students foster historical awareness of the existence of monuments around the scope of the school and their place of residence. The results showed that the web design-based ebooklet was effective in increasing students' understanding of local history, especially recognizing the figure of Major Hamid Rusdi.